(Sr,Tm)ZrO3 powders prepared by the polymeric precursor method: Synthesis, optical properties and morphological characteristics - Goncalves, M. D.; Cavalcante, L. S.; Sczancoski, J. C.; Espinosa, J. W. M. [UNESP]; Pizani, P. S.; Longo, Elson [UNESP]; Rosa, I. L. V. (Elsevier B.V., 2009)
(Sr0.995Tm0.005)ZrO3 (STZO) powders were prepared by the polymeric precursor method and heat treated at different temperatures for 2 h under oxygen flow. These powders were analyzed by X-ray diffraction (XRD), Ultraviolet-visible (UV-vis) absorption spectroscopy, photoluminescence (PL) measurements, field-emission gun-scanning electron microscopy (FEG-SEM) and energy dispersive X-ray spectrometry (EDXS). XRD patterns revealed that the powders crystallize in an orthorhombic structure without the presence of secondary phases. UV-vis absorption spectra suggest that the STZO powders heat treated at low temperatures present intermediary energy levels within the band gap as consequence of structural defects in the lattice. PL measurements indicated the presence of broad, broad/narrow and narrow bands in STZO powders. The broad bands were associated to the asymmetric STZO structure and/or p-d transitions while, the narrow bands were ascribed to f-f transitions arising from thulium ions. A simple model was proposed in order to explain the PL behavior of these powders. FEG-SEM micrographs showed that these powders are composed by several microparticles with irregular morphologies and agglomerated nature. EDX5 data were used for analyses of chemical compositional of powders. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: SrZrO3; Photoluminescence; Thulium; f-f Transitions; Microstructure